LncRNA RP5-857K21.7 inhibits PDGF-BB-induced proliferation and migration of airway smooth muscle cells through the miR-508-3p/PI3K/AKT/mTOR axis. (2nd January 2022) - Wang, Xiaojun; Xu, Lingfen; Yu, Yong; Fu, Yimin
Abstract: The continuous increase in the prevalence of asthma poses a threat to human health. Despites numerous researches, the understanding of asthma development still remain elusive, hindering the development of effective treatment. Here, we explored the role of lncRNA RP5-857K21.7 (RP5-857K21.7) in the development of asthma and its potential molecular mechanism of regulation. Airway smooth muscle cells (ASMCs) were isolated and cultured after which some of the cells were induced with PDGF-BB to build an asthma cell model, and then, qRT-PCR analysis was used to measure the expression level of RP5-857K21.7 in the cell model. Result shows that the RP5-857K21.7 is significantly downregulated in PDGF-BB-induced ASMCs cells. Through CCK-8, transwell, and flow cytometry assay, we examined the functional impact of RP5-857K21.7 on the proliferation, migration, and apoptosis of the ASMCs, respectively, and found that the overexpression of RP5-857K21.7 markedly inhibit PDGF-BB-induced ASMCs cell proliferation, migration and induce apoptosis. Bioinformatics analysis predicted that the RP5-857K21.7 could sponge miR-508-3p and result was validated through a dual-luciferase reporter assay, biotinylated RNA pull-down assay, and RIP-qRT-PCR analysis. Mechanistically, RP5-857K21.7 regulates the PI3K/AKT/mTOR pathway by endogenously sponging miR-508-3p to inhibit PDGF-BB-induced ASMCs cell proliferation, migration and induce apoptosis. The current research suggests that the RP5-857K21.7 and its associated molecular pathway (miR-508-3p/PI3K/AKT/mTOR axis) might be a useful therapeutic target for the treatment of asthma disease.